Options and Strategies for Fiscal Consolidation in India - Tapsoba, Sampawende (IMF Working Papers; Working Paper ;, 2013)
The paper uses a multi-region DSGE model to quantify the macroeconomic implications of three adjustment scenarios for India: growth-friendly, social-friendly, and a benchmark case centered on bringing down unproductive spending and strengthening the consumption tax. Simulations indicate that fiscal consolidation yields considerable long-term benefits but also entails output costs in the near term. The scenarios in which deficit reduction is accompanied by greater investment and social spending lead to better results than the benchmark case. The consolidation package alone is not enough to maximize net gains. Other factors, such as the pace and the credibility of consolidation, the concomitant implementation of structural reforms, and global economic conditions, play a critical role in the success of fiscal consolidation.